PRINCIPLES OF TAX LAW (CIPEEX, 2025)
The principles of tax law are fundamental to implementing tax laws within the Brazilian legal system. This study uses a doctrinal and legislative analysis approach, focusing on the articles of the Constitution and their interpretation in case law, to examine how these principles guide the interaction between the State and the taxpayer. First, the importance of fiscal legality is highlighted as an essential shield against arbitrary actions, emphasizing that no tax can be created or increased without the existence of a law establishing it. Next, the principle of prior notice is examined as a tool for predictability and legal certainty, guaranteeing taxpayers sufficient time to prepare for new tax obligations. Furthermore, the principle of equality is analyzed within the framework of equal treatment, avoiding unjustified privileges or discrimination. Furthermore, the principle of ability to pay is highlighted, aiming to adapt the tax burden to the taxpayer's economic capacity, highlighting the distributive and social nature of taxation. The research also takes into account the principle of prohibition of confiscation, which restricts state intervention so that taxation does not harm private property and individual dignity. The results demonstrate that, although the 1988 Federal Constitution establishes clear limits on taxation, the effectiveness of these principles depends on the correct interpretation of the courts and the responsible actions of the legislature. It is concluded that strict adherence to the principles of tax law is essential to balance the State's revenue needs and the protection of taxpayers' fundamental rights, guaranteeing fiscal justice and legal certainty in the national tax system.